1994
DOI: 10.1073/pnas.91.3.1099
|View full text |Cite
|
Sign up to set email alerts
|

CD40 ligand expression is defective in a subset of patients with common variable immunodeficiency.

Abstract: Common variable immunodeficiency (CVI) is characterized by hypogammaglobulinemia and recurrent bacterial infections due to failure of CVI B cells to differentiate in vivo into immunoglobulin-secreting plasma cells. We hypothesized that T-cell dysfunction resulting in abnormal contactmediated B-cell activation may play a prominent role in the failure of CVI B cells to produce specific antibody. We have previously shown that B-cell proliferation and IgE production after stimulation with anti-CD40 and interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
0
6

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(118 citation statements)
references
References 41 publications
9
103
0
6
Order By: Relevance
“…Table 2). (a) Genes that were underexpressed (IL-11Ra, integrin a6, CCR7) and (b) genes that were overexpressed (IFN-g, Previous reports on T cell function in CVID have indicated reduced IL-2 secretion and reduced expression of CD40L in some CVID patients [33,34]. Interestingly, both have been reported to be reduced in CCR7 -T cells [21,32].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2). (a) Genes that were underexpressed (IL-11Ra, integrin a6, CCR7) and (b) genes that were overexpressed (IFN-g, Previous reports on T cell function in CVID have indicated reduced IL-2 secretion and reduced expression of CD40L in some CVID patients [33,34]. Interestingly, both have been reported to be reduced in CCR7 -T cells [21,32].…”
Section: Discussionmentioning
confidence: 99%
“…This immune de®ciency was ®rst recognized about 45 years ago [6] but the fundamental genetic defect(s) remain unknown. While the central immune de®ciency is impaired secretion of immunoglobulin and lack of antibody production [7À9], T cell defects are also present in many, including decreased lymphocyte proliferation to mitogens and antigens [10,11], lack of antigen-primed T cells post vaccination [12,13], expansion of the CD45RO + (memory) T cells at the expense of the CD45RA + (naive) T cell population [14], de®cient expression of CD40 ligand on activated T cells [15], a tendency to accelerated T cell apoptosis, and various cytokine abnormalities [16À22]. The lack of immunoglobulin and functional antibody results in frequent sinopulmonary infections, but lymphadenopathy, splenomegaly, and granulomatous and autoimmune disease appear in signi®cant number of patients [1À5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been shown that T cells from all patients with CVI support normal Ig synthesis by B cells derived from healthy donors, suggesting expression of functional CD40L on patients' T cells and intrinsic defects in patients' B cells [17]. Whether defective CD40L expression is the underlying cause of impaired Ig production in patients with CVI is of importance, because it has been suggested that soluble CD40L may have therapeutic potential when treating patients with defective expression of CD40L [16]. It has also been reported that production of cytokines, such as IL-2, IL-4, IL-10 and IFN-g, is impaired in patients with CVI [18][19][20][21], whereas expression of the IL-6 gene is elevated [22,23].…”
Section: Introductionmentioning
confidence: 99%